Effect of heat treatment and hot isostatic pressing on the structure and mechanical properties of Inconel 939 manufactured via casting and LPBF - Sedlák, Josef; Zouhar, Jan; Pokorný, Zdeněk; Robl, Jan; Kolomý, Štěpán; Pagáč, Marek; Kouřil, Karel (Elsevier, 2025)
The powder bed fusion method is one of the metal additive technologies, which can be used for the fabrication of difficult-to-process materials, such as cobalt and nickel superalloys. Inconel 939 is an example of a nickel superalloy widely used in constructions subjected to high temperatures such as industrial gas turbines. The current paper studies the effect of heat treatment and Hot Isostatic Pressing (HIP) on the structure and mechanical properties of additively manufactured (AM) Inconel 939. Mechanical properties i.e., tensile yield strength, ultimate tensile strength, and creep resistance were observed after the heat treatment (comprised of annealing and subsequent aging), HIP, and compared to the conventionally casted material. HIP post-process caused an increase of 5.73 % and 3.81 % in ultimate tensile strength at the room temperature as well as at the elevated temperature. A detailed analysis of the microstructure of AM and casting samples via light and electron microscopy was performed. The maximum grain sizes in AM samples were similar (122.9 m and 127.2 m in the axis and periphery, respectively), while the grain size in casting samples exhibited a mean equivalent circle diameter of 440 m in the axial region and 398 m in the vicinity of the peripheral region.
Keywords: Inconel 939; Powder bed fusion; Hot isostatic pressing; Creep resistance; Microstructure; Mechanical properties